Analisis Pengungkapan Laporan Sosial dan Lingkungan dalam Akuntansi Pertanggungjawaban Sosial Perusahaan (Studi pada Bursa Efek Jakarta) - Rajafi, Lalu Roby; Irianto, Gugus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2007)
This research is about to analyze social and environmental disclosure of industries in Indonesia as part o f triple bottom line reporting in corporate social responsibility accounting with seeing their annual report at year 2005. This research focusses on the analysis of social information disclosure’s form and the analysis of the average differences of disclosure topics among industries groups listed at Jakarta Stock Exchange in the year of 2005. This research uses descriptive method to describe disclosure’s forms applied and the average differences of disclosure topics among industries groups listed at Jakarta Stock Exchange. The annual reports were analyzed using content analysis method with Kruskall Walis’s non-parametric statistical test as a tools to examine the average differences of disclosure topics within these industries groups. Based on the Kruskal Wallis’s non-parametric test conducted, there are some significant differences among company groups in disclose environmental and employment issues, while the disclosure of society issues tend to be illustrated in the same form. Each of this company groups are having a different perception about the disclosure topics they present in their Annual Report. Consequently, this has resulted a different topics to be disclosed: Agriculture and Mining emphasize on environtmental issues, Consumer Goods Industry (CGS), Property, Real Estate & Building Construction (PRE&BC), and Infrastructure, Utilities & Transportation (IU&T) are likely lean on employment issues, while Finance and Trade, Service & Investment (TSI) emphasize on society issues. This was happened because of the essential differences on company’s activities type, company’s sensitivities, and company’s goals. Key words: Triple bottom line reporting, social disclosure, and environmental disclosure